Fatigue damage analysis of plain and steel fiber-reinforced concrete material based on a stiffness degradation microplane model - Qin, Changjin; Dong, Xiaogang; Wu, Biao; Cai, Lidong; Wang, Shaohua; Xia, Qing (Frontiers in Materials, 2024)
Steel fiber-reinforced concrete material has garnered significant attention in structure design due to its excellent resistance to fatigue damage. The application of the plain concrete microplane model is extended to steel fiber-reinforced concrete by modifying the stress-strain boundary conditions on the microplane and then extended to fatigue damage analysis by considering fatigue-related material stiffness, mainly concerned with tensile damage, mainly concerned with tensile damage. The normal positive strain on the micro-plane is regarded as the fatigue variable, and the fatigue history variable is the accumulation of the fatigue variable during the loading. The relationship between the fatigue history variable and the material stiffness fatigue degradation function is established. In the numerical implementation, the crack band model is combined to reduce the mesh sensitivity caused by strain localization. During the numerical simulation, the parameters of plain concrete, steel fiber-reinforced concrete, and the material fatigue degradation function can be calibrated sequentially, requiring only a few benchmark tests for accurate parameter calibration. The numerical results show that this model can be used for the fatigue damage analysis of plain concrete and steel fiber-reinforced concrete material. It is expected to be used for the refined analysis of concrete structures under complex loading conditions and structural forms in the future, providing convenience to engineering design, evaluation, and optimization.